1996
DOI: 10.1002/crat.2170310509
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Structure of Bipyridine Coordinated with Copper (II): [Cu(bipy) (H2O)3] · (NO3)2

Abstract: The crystal structure of the mononuclear copper (II) complex containing a 2,2′‐bipyridine and three water molecules, [Cu(bipy) (H2O)3]. (NO3)2, is reported. The copper coordination polyhedron is a five‐coordinated distorted pyramid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…52 The absorption band appearing in the region 1800-1700 cm -1 , may be attributed to the free NO 3 ion present in the lattice of the molecule. 54,55 The IR spectrum of the compound 2 ( Figure S8) can be assigned similar to that of compound 1. The peaks observed at 771 cm -1 and 615 cm -1 , is indicative of the bidentate N-N coordination of the bpy to the Dy centre.…”
Section: Ir Spectroscopymentioning
confidence: 85%
“…52 The absorption band appearing in the region 1800-1700 cm -1 , may be attributed to the free NO 3 ion present in the lattice of the molecule. 54,55 The IR spectrum of the compound 2 ( Figure S8) can be assigned similar to that of compound 1. The peaks observed at 771 cm -1 and 615 cm -1 , is indicative of the bidentate N-N coordination of the bpy to the Dy centre.…”
Section: Ir Spectroscopymentioning
confidence: 85%
“…X-ray quality light blue-greenish and blue prismatic crystals in an approximate ratio of 1:1 were formed, which were separated manually and dried in air. X-ray crystallography revealed that the blue prisms correspond to complex 5·4H 2 O and the light blue-greenish plates correspond to the known [9] complex 6. FTIR for 5·4H 2 0.0359 [b] 0.0412 [c] 0.0461 [d] 0.0339 [e] 0.0467 [f] wR 2 [a] 0.0971 [b] 0.1018 [c] 0.1211 [d] 0.0894 [e] 0.1173 [f] [a] w = 1⁄[σ Light blue needlelike crystals were formed upon standing of the final light blue solution in a closed vial at ca.…”
Section: Methodsmentioning
confidence: 98%
“…[9] As in the HL -reaction system, the three complexes have been isolated from the same reaction solution, either as mixtures or in the pure form, depending on their different solubilities. Complex 5·4H 2 O contains a tetranuclear cation that is structurally similar to that present in 3·2H 2 O and neutral tetrahedral Li I complexes.…”
Section: Concluding Comments and Perspectivesmentioning
confidence: 99%
“…2,2 0 -Bipyridine has been a useful molecule and is being widely used by various research groups involving it as a ligand for complex formation [21][22][23][24][25]. Recently, much attention has been given to energetic transition metal perchlorate complexes having heterocyclic ligands such as imidazole [26], 4,4 0 -bipyridine [27], hexamethylenetetramine [28,29], 3(5)-hydrazino-4-amino-1,2,4-triazole (HATr) [30], 4-amino-1,2,4-triazole [31], 2,2 0 -bipyridine [1][2][3], 2-aminopyridine [32] and 4-aminopyridine [33].…”
Section: Introductionmentioning
confidence: 99%